Profil Acute Kidney Injury pada Anak yang Dirawat di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado - Ango, Putri C.; Umboh, Adrian; Salendu, Praevilia M. (Medical Scope Journal, 2025)
Abstract: Acute kidney injury (AKI) is a clinical condition as evidenced by elevated levels of creatinine and urea, as well as a decrease in glomerular filtration rate (GFR). This study aimed to determine the profile of AKI in children admitted to the Pediatric Department of Prof. Dr. R. D. Kandou General Hospital, Manado, during the period from January 2020 to August 2023. This was a retrospective and descriptive study with an observational approach and a cross-sectional design. Samples included all children who were diagnosed with AKI. The results obtained 121 patients with AKI, aged 1 month to 18 years, comprising 53.7% males, 46.3% females. Pre-renal AKI accounted for 61.1%, while renal AKI was 38.9%. Common clinical features included fever (75.3%), respiratory distress (61.2%), edema (49.7%), oliguria (93.3%), proteinuria (54.5%), azotemia (100.0%), microscopic hematuria (61.2%), leukocyturia (43.8%), hyponatremia (53.0%), hypocalcemia (47.2%), hypochloremia (48.0%), sepsis (42.1%), septic shock (17.3%), and metabolic acidosis (2.4%). In conclusion, AKI was most commonly found in the age group of 11-15 years, with a higher prevalence in males than females. The most common etiology was pre-renal AKI, with oliguria, fever, and respiratory distress being the most common clinical symptoms. Laboratory examinations commonly showed azotemia, hematuria, proteinuria, and leukocyturia. Keywords: acute kidney injury; children; clinical features; complication   Abstrak: Acute Kidney Injury (AKI) adalah sebuah keadaan klinis dimana terjadi peningkatan kreatinin dan urea serta penurunan laju filtrasi glomerulus (LFG). Penelitian ini bertujuan untuk mengetahui profil AKI pada anak yang dirawat di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2020-Agustus 2023. Jenis penelitian ialah deskriptif retrospektif dan observasional dengan desain potong lintang. Sampel penelitian ini ialah semua anak yang dirawat dan didiagnosis AKI. Hasil penelitian mendapatkan 121 pasien dengan diagnosis AKI, usia 1 bulan-18 tahun, laki-laki 53,7%, perempuan 46,3%. AKI pre-renal 61,1%, AKI renal 38,9%. Demam 75,3%, sesak napas 61,2%, edema 49,7%, oliguria 93,3%, proteinuria 54,5%, azotemia 100,0%, hematuria mikroskopis 61,2%, leukosituria 43,8%, hiponatremia 53,0%, hipokalsemia 47,2%, hipokloremia 48,0%, sepsis 42,1%, syok sepsis 17,3%, dan asidosis metabolik 2,4%. Simpulan penelitian ini ialah AKI ditemukan tersering pada rentang usia 11-15 tahun, lebih sering pada laki-laki dibandingkan perempuan, etiologi terbanyak ialah AKI pre-renal, gejala klinis tersering ialah oliguria, demam dan sesak napas. Pemeriksaan laboratorium tersering ditemukan azotemia, hematuria, proteinuria, serta leukosituria. Kata kunci: acute kidney injury; anak; gangguan ginjal akut; komplikasi